2016
DOI: 10.1016/j.taap.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Chronic plus binge ethanol exposure causes more severe pancreatic injury and inflammation

Abstract: Alcohol abuse increases the risk for pancreatitis. The pattern of alcohol drinking may impact its effect. We tested a hypothesis that chronic ethanol consumption in combination with binge exposure imposes more severe damage to the pancreas. C57BL/6 mice were divided into four groups: control, chronic ethanol exposure, binge ethanol exposure and chronic plus binge ethanol exposure. For the control group, mice were fed with a liquid diet for two weeks. For the chronic ethanol exposure group, mice were fed with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…In the NIAAA mouse model, ad libitum EtOH feeding for 10 days (5% v / v , 10 d) resulted in a BAC of ~180 mg/dL, but 10 days combined with a single binge (10 d + 1 B) induced BAC levels as high as ~400 mg/dL 1 h and 2 h following the binge bolus [ 20 ]. In mice fed an EtOH-containing liquid diet (5% EtOH) for two weeks and administered EtOH binges (5 g/kg) during the last three days, BAC was significantly increased 1 h post-binge in chronic-binge EtOH group compared to chronic EtOH alone (406 ± 76 mg/dL vs. 93 ± 69 mg/dL after one binge and 428 ± 84 mg/dL vs. 82 ± 43 mg/dL after three binges) [ 60 ]. Similarly, in a rat model [ 61 ], chronic EtOH feeding for four weeks (5% v / v ) followed by either single (5 g/kg) or repeated binge EtOH administration (5 g/kg, three doses, 12 h intervals) significantly increased BAC levels (~40 mM (175.7 mg/dL) and ~120 mM (540.3 mg/dL) respectively) compared to chronic alcohol feeding alone (~20 mM (101.5 mg/dL)), and these increases were associated with augmented liver injury.…”
Section: Binge Alcohol Drinking Pattern and Blood Alcohol Concentrmentioning
confidence: 99%
See 2 more Smart Citations
“…In the NIAAA mouse model, ad libitum EtOH feeding for 10 days (5% v / v , 10 d) resulted in a BAC of ~180 mg/dL, but 10 days combined with a single binge (10 d + 1 B) induced BAC levels as high as ~400 mg/dL 1 h and 2 h following the binge bolus [ 20 ]. In mice fed an EtOH-containing liquid diet (5% EtOH) for two weeks and administered EtOH binges (5 g/kg) during the last three days, BAC was significantly increased 1 h post-binge in chronic-binge EtOH group compared to chronic EtOH alone (406 ± 76 mg/dL vs. 93 ± 69 mg/dL after one binge and 428 ± 84 mg/dL vs. 82 ± 43 mg/dL after three binges) [ 60 ]. Similarly, in a rat model [ 61 ], chronic EtOH feeding for four weeks (5% v / v ) followed by either single (5 g/kg) or repeated binge EtOH administration (5 g/kg, three doses, 12 h intervals) significantly increased BAC levels (~40 mM (175.7 mg/dL) and ~120 mM (540.3 mg/dL) respectively) compared to chronic alcohol feeding alone (~20 mM (101.5 mg/dL)), and these increases were associated with augmented liver injury.…”
Section: Binge Alcohol Drinking Pattern and Blood Alcohol Concentrmentioning
confidence: 99%
“…For example, Matyas et al employed variations of the NIAAA model (such as 10 d + 1 B, 20 d + 2 B, and 40 d + 4 B), and demonstrated that chronic-binge EtOH feeding in mice leads to alcoholic cardiomyopathies characterized by increased myocardial oxidative/nitrative stress, impaired mitochondrial function and biogenesis, cardiomyocyte hypertrophy, and enhanced cardiac steatosis [ 58 ]. Paradigms of binge EtOH exposure in rodents were utilized to study the impact of drinking patterns on alcoholic pancreatitis [ 59 , 60 ]. In these studies, male C57BL/6 mice were maintained on a standard rodent chow diet and administered EtOH binges (5 g/kg) daily for 10 days (10 B) [ 59 ], or were fed an EtOH liquid diet (5% EtOH) for two weeks with EtOH binges daily during the last three days (2 w + 3 B) [ 60 ].…”
Section: Rodents Models Of Ald Utilizing Binge Ethanol Administratmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it was published in 2010 11, 12 , the chronic-plus-binge model has been widely used by many investigators, and many novel mechanisms underlying liver inflammation and injury in this model have been revealed. Recently, the chronic-plus-binge ethanol mouse model has also been used to examine other organ damage such as the heart 13 , pancreas 14 , and adipose tissues 15 . In addition, this model was also established in rats 16, 17 .…”
mentioning
confidence: 99%
“…Chronic alcohol intake suppresses glucokinase transcriptional activity, which induces β‐cell dysfunction in C57BL/6J male mice (Kim et al., ). Alcohol is also known to decrease β‐cell mass by increasing oxidative stress and inflammation in rats, leading to increased β‐cell apoptosis (Ren et al., ; Zhao et al., ). The decrease in β‐cell mass is also associated with a decrease in β‐cell proliferation (Koko et al., ).…”
mentioning
confidence: 99%